Pandora's locks : the opening of the Great Lakes-St. Lawrence Seaway - Alexander, Jeff, 1962- (UPCC book collections on Project MUSE., 2009)
The St. Lawrence Seaway was considered one of the world''s greatest engineering achievements when it opened in 1959. The 1 billion project-a series of locks, canals, and dams that tamed the ferocious St. Lawrence River-opened the Great Lakes to the global shipping industry. Linking ports on lakes Superior, Michigan, Huron, Erie, and Ontario to shipping hubs on the world''s seven seas increased global trade in the Great Lakes region. But it came at an extraordinarily high price. Foreign species that immigrated into the lakes in ocean freighters'' ballast water tanks unleashed a biological.